Fractional dynamics and analysis for a lana fever infectious ailment with Caputo operator - Acay, Bahar; İnç, Mustafa; Mustapha, Umar Tasiu; Yusuf, Abdullahi (Pergamon-Elsevier Science Ltd, 2021)
This study provides a deep insight into the complex process of the lana fever infectious disease model by employing the advantages of a non-local fractional operator called Caputo derivative. The fractional-type lana fever model possessing memory effect and hereditary properties allows us to comprehend the dynamics of the disease transmission in detail. For this purpose, we introduce some crucial theoretical and numerical results for the suggested disease model with the aid of the Caputo fractional derivative. The existence and uniqueness of the solution of lana fever system are shown through the fixed point theorem. Moreover, we find the most sensitive parameters under the forward sensitivity index in relation to reproduction number R-0. Also, some basic properties of the lana fever model such as virus-free equilibrium point, reproduction number, virus endemic equilibrium point, local and global stability are presented by using the Caputo derivative. On the other hand, further analysis of the fractional version of the lana fever model shows that the disease-free equilibrium is locally asymptotically stable when R-0 < 1, and also the endemic equilibrium of the model under investigation is globally asymptotically stable when R-0 > 1. Additionally, numerical results are presented to observe the advantages of the non-local fractional differential operator of Caputo. (C) 2021 Elsevier Ltd. All rights reserved.
Keywords: Fractional derivatives; Lana fever; Fractional modeling; Mathematical biology